Knowledge, attitude and practice of prophetic food consumption among undergraduate students of Universiti Sains Malysia, Health Campus, Kubang Kerian, Kelantan - Shahirah Ayuni Anwar; Wan Faizah Wan Yusoff (Penerbit Universiti Kebangsaan Malaysia, 2022)
Islam is a way of life for many people. Muhammad (PBUH) is the perfect example in every way. Halal and tayyib food is essential in Islam for prosperity and well-being. Food consumption can potential to influence human growth of akhlaq, morality, and psychology. The purpose of this study was to identify the levels of knowledge, attitude, and practice of prophetic food consumption among undergraduate students of USM, Health Campus. The current study was conducted at the USM Health Campus in Kelantan from September 2021 to February 2022. A total of 143 students were recruited for this cross-sectional study using the convenience sampling method. A questionnaire based on the prophetic food consumption details was developed, consisting of four sections: demographic data, knowledge, attitude, and consumption practice. The results showed that 21.7% of the respondents took prophetic food, 31% had a positive attitude and there were 48.3% less in consuming prophetic food. There was a significant difference in the mean knowledge score between age group, mean knowledge, attitude and practice scores between ethnicity, mean knowledge, attitude and practice between religion, mean knowledge and attitude scores between the fields of study groups, and mean knowledge, attitude, between the level of study, according to Man Whitney Test and Kruskal Wallis statistical tests. Based on the Spearman correlation test, a positive correlation was found between knowledge and attitude (r = 0.391, p = 0.000), knowledge and practice (r= 0.200, p=0.017), and attitude and practice (r = 0.314, p=0.000). The findings may help the healthcare providers and authorities plan awareness programs for the young consumers on practising prophetic diet daily and to understand the evolution of beliefs related to prophetic food as effective medications. Finally, prophetic food must be emphasised and shared with multi-religious university students to be more familiar with the relevant health and sustainability issues.